Latihan Pemanfaatan Mendelay Untuk Citasi dan Referensi Bagi Kadet Mahasiswa Permesinan Kapal Unhan RI - Manesi, Damianus; Zaini, Ansori; Silitonga, Tatar Bonar; Tnunay, Imanuel (Abdi Masyarakat, 2023)
The ability to write is an absolute requirement for students, especially related to the completion of assignments given by lecturers up to the final project. Obstacles arise because most students are still ignorant about citations and reference management, so plagiarism is rife. This service aims to train students to understand and master an application to assist in making citations and management of references using the Mendeley application. The service is carried out in three stages, namely the preparation, implementation and evaluation stages. Participants were 50 students of the Indonesian Defense University ship engineering study program. In its implementation, the training material is divided into 4, namely Mendeley installation techniques, citation techniques and reference management, introduction of Mendeley tools and demonstrations as well as training in using Mendeley. The material is delivered by lecture, discussion, demonstration and practice methods. The results of the service activities show that at the end of the training activities all participants are familiar with, able to install, and able to operate the application to make citations and bibliography properly and correctly. Participants have also been able to prove good citation and reference management for 30 articles. It is hoped that this training can be continued in the form of mentoring because it has a significant positive impact on students.